Investigating the Relationship Between Soil Stabilization Techniques and Sustainable Foundation Engineering Practices - Ina Elvina; Agripina Pereira Freitas; Winarno, Basuki (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study investigates the relationship between soil stabilization techniques and sustainable foundation engineering practices, focusing on the environmental, economic, and technical aspects of various stabilization methods. The research employs a qualitative approach, specifically a literature review, to explore the effectiveness of conventional soil stabilization techniques, such as cement and lime, as well as emerging sustainable alternatives, including the use of industrial byproducts like fly ash and innovative microbial stabilization. The findings reveal that while traditional methods are effective in enhancing soil properties, they are associated with significant environmental and economic drawbacks, particularly due to high CO2 emissions from cement production. On the other hand, alternative techniques such as fly ash stabilization and microbial-based solutions offer significant environmental benefits by reducing carbon footprints and providing cost-effective, sustainable alternatives. Additionally, the integration of environmental, economic, and technical factors into decision-making frameworks is essential for promoting sustainable foundation engineering practices. The study highlights the importance of adopting green technologies to achieve sustainability in foundation engineering and recommends further research into the long-term performance and scalability of alternative stabilization methods. Moreover, future studies should focus on developing standardized guidelines and exploring the role of policy and regulations in supporting sustainable practices in construction.